Предмет: Математика, автор: Сережа90

- 3 целых 1/2 - ( - 1 целая 3/4)
2 целых 2/3 - 3 целых 5/9
-1 целая 5/8 + 3/4

Ответы

Автор ответа: jekadva
0
-3 frac{1}{2} -(-1 frac{3}{4} )=- frac{7}{2} + frac{7}{4} = frac{-14+7}{4}  = - frac{7}{4} =-1 frac{3}{4}   \  \ 2 frac{2}{3} -3 frac{5}{9} =2 frac{6}{9} -3 frac{5}{9} =-(2 frac{14}{9} -2 frac{6}{9} )=- frac{8}{9}  \  \ - frac{5}{8} + frac{3}{4} =-(1 frac{5}{8} - frac{6}{8} )=-(frac{13}{8} - frac{6}{8}) =- frac{7}{8}
Автор ответа: Сережа90
0
спс
Автор ответа: Сережа90
0
объясни 3 пример
Похожие вопросы
Предмет: Математика, автор: 050708gvo
Предмет: Алгебра, автор: Аноним